Approximation of Functions from the Isotropic Nikol’skii–Besov Classes in the Uniform and Integral Metrics - Yanchenko, S. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We obtain the exact-order estimations for the approximation of the isotropic Nikol’skii–Besov classes of functions of several variables by the de la Vallée-Poussin-type sums in metrics of the spaces $L_{∞}(ℝ^d)$ and $L_1(ℝ^d)$.